2014
DOI: 10.1007/s13762-014-0690-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on tetracycline sorption by Pachydictyon coriaceum and Sargassum hemiphyllum

Abstract: This study compared the biosorption of tetracycline, an antibiotic commonly used to treat bacterial infections, in aqueous solution under various conditions using two brown seaweeds commonly found in Hong Kong waters-Pachydictyon coriaceum and Sargassum hemiphyllum. Two environmental effects (temperature and shaking speed) and two chemical effects (pH and salinity) were investigated to determine the optimal conditions for sorption of tetracycline by biomass. It was found that the maximum biosorption capacity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 59 publications
0
9
1
Order By: Relevance
“…Li and Wong found similar behavior in the efficiency of Tc removal using the biomass of Pachydictyon coriaceum and Sargassum hemiphyllum as biosorbents. 39 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li and Wong found similar behavior in the efficiency of Tc removal using the biomass of Pachydictyon coriaceum and Sargassum hemiphyllum as biosorbents. 39 …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that pH variations affect the removal of tetracycline depending on the sorbent. Li and Wong found that the adsorption capacity of Tc increases with increasing pH by using biomasses of Pachydictyon coriaceum and Sargassum hemiphyllum . Ding et al found the maximum Tc removal at pH between 6 and 8 with dry biomass of acid-treated (and untreated) roots of Alternanthera philoxeroides …”
Section: Resultsmentioning
confidence: 99%
“… Treatment Materials Antibiotic Operating conditions Disadvantages Ref. Adsorption processes Anionic surfactant sodium dodecyl sulfate (SDS) Amoxicillin Ampicillin Contact time: 40 min Agitation speed: 350 rpm Temperature: 40 °C pH: 4 Low removal capacities; difficult separation; secondary environmental pollution; unsatisfactory recycling ability [13] KOH-modified biochar Norfloxacin Sulfamerazine Oxytetracycline Temperature: 15–35 °C pH 3–9 [14] Graphene oxide/cellulose nanofibril hybrid aerogel Doxycycline Chlortetracycline Oxytetracycline Tetracycline Temperature: 25 °C [15] Pyrogenic carbonaceous materials Ciprofloxacin Contact time: 72 h Temperature: 25 °C pH 7.5 and 9.5 [16] Clean and dried Kigelia pinnata modified with ionic liquid Ibuprofen Ketoprofen Ampicillin Diclofenac pH 2.5 or 5 [17] Manure-derived biochars Lincomycin pH 6 or 10 [18] Lanthanum modified diatomite Tetracycline antibiotics Contact time: 24 h pH 3–10 [19] Adsorption processes Grape stalk Ofloxacin Chrysoidine pH 4, 7, and 9 Low removal capacities; difficult separation; secondary environmental pollution; unsatisfactory recycling capacity [20] Cleaned and dried Pachydictyon coriaceum and Sargassum hemiphyllum Tetracycline Temperature: 15–35 °C pH 3–9 Salinity: 0–100 mM NaCl [21] Spent mushroom substrate Sulfamethyldiazine Sulfamethazine Sulfathiazole Sulfamethoxazole Temperature: 15 °C pH 3–11...…”
Section: Introductionmentioning
confidence: 99%
“…An attractive alternative to the methods listed above is adsorption, due to its simplicity, safety, economic feasibility, and removal efficiency at low sorbent concentrations. A wide variety of adsorbents have been studied for tetracyclines removal from aqueous solutions: carbon-based materials (biochar, activated carbon, carbon nanotubes, graphene) [16], silica [17], pumice stone [18], biopolymers (chitosan and modified alginate) [19,20], algae [21,22], metal-organic frameworks -MOFs [23][24][25], magnetic nanocomposites [26][27][28].…”
Section: Introductionmentioning
confidence: 99%